Initiating Educational Policies for Older Adults: Analysis of the Implementation of Lifelong Learning Concepts - Suryadi Suryadi; Nana Priajana (International Journal of Education and Humanities, 2021)
This study aims to identify several comparisons of lifelong learning concepts and models for older adults to remain active and productive. The method employed in this study is a literature review investigating research articles from the internet using the Science Direct, Google Scholar, and Research gate sites. Details of the search strategy for article eligibility using the PRISMA format (Identification, Screening, Eligibility, Included). The analysis of selected research articles' reveals that older adults' education concepts and models in developed countries are more well established and concerned. The model of older adults' education in demand has religious, spiritual, and spiritual dimensions. The appropriate model is entirely rational due to closely related to the local wisdom of the Indonesian people. The majority of studies conducted show the need for support from stakeholder policies. The support from the community and family is still quite dominant, so that the potential of the elderly population who are still productive, independent, and contributive to society is necessary